The Word-Formation Process of Konshugo in Japanese Beauty News Articles - Az Zahra Khoirala Mustafa; Elizabeth Ika Hesti Aprilia Nindia Rini (Manunggal Halim Jaya, 2026)
This research examines the word formation process and meaning of konshugo (混種語) In Japanese beauty news articles sourced from the Fashion Press platform for the period January 2025 to April 2026, Japanese recognizes vocabulary classification based on its origins, goshu (語種) become wago, kango, and gairaigo, as well as a hybrid form of the three, known as konshugo. The rapid evolution of discourse surrounding Japanese beauty has spurred the emergence of lexical innovations known as konshugo hybrid compounds which remain largely undocumented in conventional dictionaries and standard teaching materials. This study employs a qualitative descriptive approach, utilizing the non-participatory observation and note-taking techniques for data collection, alongside the distributional method and the immediate constituent analysis technique for data analysis; the study is grounded in Tsujimura’s (2014) theory of word formation and Akimoto’s (2002) classification of konshugo composition. The study identified 50 instances of konshugo formed through one (8 instances), two (30 instances), and three (12 instances) word-formation processes including compounding, borrowing, affixation, and clipping that interacted with one another in a stepwise manner. In terms of elemental composition, the combinations of wago+gairaigo and gairaigo+kango are the most productive patterns. Regarding meaning, the data yielded 30 instances of lexical meaning and 20 instances of contextual meaning. These findings indicate that *konshugo* serves as both a productive word-formation strategy and a branding tool within Japanese beauty discourse, creating terms that are lexically efficient and commercially appealing to readers.